A Novel, Well‐Resolved Direct Laser Bioprinting System for Rapid Cell Encapsulation and Microwell Fabrication. Issue 9 (5th February 2018) - Wang, Zongjie; Jin, Xian; Tian, Zhenlin; Menard, Frederic; Holzman, Jonathan F.; Kim, Keekyoung
Abstract: A direct laser bioprinting (DLBP) system is introduced in this work. The DLBP system applies visible‐laser‐induced photo‐crosslinking at a wavelength of 405 nm using the photoinitiator VA‐086. It is shown that such a system can fabricate vertical structures with fine features (less than 50 µm) and high cell viability (greater than 95%). Experimental characterizations and theoretical simulations are presented, and good agreement is seen between the experiments and theory. The DLBP system is applied to the fabrication of (1) cell‐laden hydrogel microgrids, (2) hydrogel microwells, as well as a test of (3) cell encapsulation, and (4) cell seeding. The DLBP system is found to be a promising tool for bioprinting. Abstract : Existing bioprinting methods have difficulties in achieving high cell viability and fine resolution simultaneously. This work introduces a new type of bioprinting method named "direct laser bioprinting" (DLBP). The DLBP utilizes the focused laser beamspot to selectively photo‐crosslink a hydrogel prepolymer solution. It is proven to perform the rapid fabrication of cell‐laden hydrogels with fine resolution and high cell viability.